2017
DOI: 10.1007/s13197-017-2883-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of osmotic dehydration treatment on volatile compound (Myristicin) content and antioxidants property of nutmeg (Myristica fragrans) pericarp

Abstract: The effects of osmotic dehydration (OD) treatment on volatile compound (myristicin) content and the antioxidant capacity of nutmeg () were studied. Fresh nutmeg pericarps were treated with varying sugar concentrations (60, 70, 80%) with different soaking periods at ambient temperature. The OD-treated nutmeg extracts were analyzed for myristicin content via Gas Chromatography Flame Ionization Detector. The phenolic content and antioxidant capacity were analyzed using Follin-Ciocalteu and a free radical scavengi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
2
6
1
Order By: Relevance
“…The high viscosity of the solution possibly acted as a 2014). Previous findings also support these results where the best antioxidant activity was observed at higher concentrations (Rahman et al 2018). Reported literature also shows that osmotic stress can increase the enzymatic activity, which in turn promotes key chemical reactions such as esterification (Escriche et al 2006).…”
Section: The Impact Of Sucrose Solution On Tpc Dpph Radical Scavenging Activity and P-cymenesupporting
confidence: 68%
“…The high viscosity of the solution possibly acted as a 2014). Previous findings also support these results where the best antioxidant activity was observed at higher concentrations (Rahman et al 2018). Reported literature also shows that osmotic stress can increase the enzymatic activity, which in turn promotes key chemical reactions such as esterification (Escriche et al 2006).…”
Section: The Impact Of Sucrose Solution On Tpc Dpph Radical Scavenging Activity and P-cymenesupporting
confidence: 68%
“…The increment in myristicin was also reported in specimens of nutmeg (Myristica fragrans Houtt.) subjected to dehydration stress: the higher content of this compound was found in the samples growing in the higher concentration of osmotic solution [26].…”
Section: Discussionmentioning
confidence: 95%
“…Investigation studies of antioxidant activity were conducted with myristicin isolated or present in extracts and essential oils obtained from the following plant species: Dorema glabrum (14% myristicin); Naturtium officinale (57% myristicin); Athamanta turbith (52% myristicin), Heracleum transcaucasicum and Heracleum anisactis (containing 96.87% and 95.15% myristicin respectively) and Myristica fragrans (containing 8% to 11% myristicin) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained showed that, in vivo, isolated myristicin (high purity) was able to increase the concentration and activity of antioxidant enzymes: catalase, superoxide dismutase, glutathione peroxidase and glutathione reductase, as well as decreasing the levels of lipid peroxidation (Figure 2). The essential oils containing myristicin also showed good antioxidant activity in vitro, with the exception of the oil from the plant Athamanta turbith, whose activity was relatively low [16][17][18][19][20][21][22]. One of the studies used Myristica fragrans (nutmeg) essential oil containing myristicin, the same oil without myristicin, and also myristicin alone.…”
Section: Antioxidant Activitymentioning
confidence: 99%